2020
DOI: 10.3390/brainsci10110831
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Occludin and Claudin-5 in Acute Stroke Are Correlated with the Type and Location of Stroke but Not with the Neurological State of Patients—Preliminary Data

Abstract: The blood–brain barrier is the structure (BBB), which isolates the central nervous system from the external environmental. During a stroke, the BBB gets damaged, which is accompanied by changes in the concentrations and distributions of claudin-5, occludin, ZO-1, and other building blocks of the BBB. The aim of this study was to assess the concentrations of selected components of the BBB—occludin, claudin-5, and zonulin (ZO-1)—and to define a potential relationship between the concentrations of these three sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…We then examined claudin-5 level from hippocampal tissues of these mice and found a decrease of claudin-5 both in protein (t = 1.263; P = 0.021; Figure 1C , 1D ) and mRNA level (t = 1.013; P = 0.003; Figure 1E ). To investigate if supplementation of claudin-5 had effects on cognitive ability of APP/PS1 mice, we intravenously injected different concentration of claudin-5 (1, 2, 4 μM) [ 31 , 32 ] into the APP/PS1 mice. We found that intravenous injection of claudin-5 at 4 μM but not 1 or 2 μM restored decreased claudin-5 mRNA level (F 4,25 = 35.845; P = 0.041; Figure 2A ) without affecting other claudins ( Supplementary Figure 1A ) in APP/PS1 mice of the hippocampal region.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined claudin-5 level from hippocampal tissues of these mice and found a decrease of claudin-5 both in protein (t = 1.263; P = 0.021; Figure 1C , 1D ) and mRNA level (t = 1.013; P = 0.003; Figure 1E ). To investigate if supplementation of claudin-5 had effects on cognitive ability of APP/PS1 mice, we intravenously injected different concentration of claudin-5 (1, 2, 4 μM) [ 31 , 32 ] into the APP/PS1 mice. We found that intravenous injection of claudin-5 at 4 μM but not 1 or 2 μM restored decreased claudin-5 mRNA level (F 4,25 = 35.845; P = 0.041; Figure 2A ) without affecting other claudins ( Supplementary Figure 1A ) in APP/PS1 mice of the hippocampal region.…”
Section: Resultsmentioning
confidence: 99%
“…Rifaximin treatment significantly reduced the serum concentrations of proinflammatory cytokines IL-1β, IL-6, and TNF-α in the MitoPark mice (representative image, Figure 2 A and analysis, Figure 2 B, Supplementary Figure S1 for the full blot). Furthermore, the rifaximin-treated MitoPark mice had a significant reduction in blood claudin-5 and occludin, which are markers of BBB permeabilization [ 26 , 27 ] (representative image in Figure 2 C and analysis results in Figure 2 D). These results suggested that the robust anti-inflammatory effect of rifaximin prevented leaky gut syndrome-associated systemic inflammation and subsequent BBB permeabilization.…”
Section: Resultsmentioning
confidence: 99%
“…After an initial drop from the level in naïve animals, CLN-5 + MFI in both blood and CNS trended upward gradually from D6 to D12, then peaked sharply at D15. As at or around this time of disease there is heightened inflammation, when TJs are being broken down and considerable CLN-5 protein is lost from the CNS vasculature [ 21 , 44 , 45 ], B cells may have acquired some CLN-5 protein that was liberated into the circulation, the inter-endothelial cleft, and/or perivascular space through proteolysis or other means [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%